Fragmentation of Investment Regulations in Indonesia: An Analysis of Normative Disharmony and the Reform Agenda from an Investment Certainty Perspective - Irwan Hasan; La Ode Husen; Abdul Qahar (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to analyze the fragmentation of investment regulations in Indonesia, emphasizing the identification of forms of normative disharmony and formulating a regulatory reform agenda from an investment certainty perspective. The main focus of the study is to examine the extent to which the lack of synchronization between laws and regulations, both vertically and horizontally, impacts the effectiveness of the national investment legal system. The research method used is normative legal research with a library research approach and a systematic literature review, supported by a regulatory approach, a conceptual approach, and a comparative approach. Data analysis techniques are descriptive-prescriptive to outline legal issues and provide normative recommendations. The results show that regulatory fragmentation occurs due to the complexity of the multi-layered legal system, weak institutional coordination, and inconsistencies in norms across sectors and levels of government. This disharmony gives rise to normative conflicts, overlapping authorities, and unclear legal terminology, which have resulted in increased legal uncertainty, transaction costs, and investment risks. Furthermore, the regulatory reforms that have been implemented have not been fully effective due to obstacles in harmonization and implementation. The research findings confirm the need for comprehensive and integrated regulatory reform through legal harmonization, institutional strengthening, and optimization of technology-based licensing systems to create legal certainty and increase national investment competitiveness.